(untitled) (Journal of the College of Basic Education, 2026)
The comparative lesson is one of the sciences and theses that were influenced by dogmatic thought, specifically in the first theses, and the most prominent effect of this was the comparative study moving away from its nature, and its tendency towards a literary bias away from the objectivity that constitutes the most prominent feature of the comparative lesson, and the study of Arabic and Western literature can feel The effect of this thought from time to time. This research reviews the nature of the impact of dogmatic thought on the Arab and Western heritage, specifically in the comparative study, and reveals the pioneers of this thought, as well as the literary media in the East and West who stood against this thought in the comparative study and tried through their writings or through their proposals in conferences on literature. Comparative scholars should provide an objective model for the comparative lesson, and remove from it any dogmatic thought that prevents the universality of comparative literature.